A study on relationship between macroeconomic variables with non performing loan of Islamic banking in Malaysia / Raziana Sabtu (Faculty of Business and Management, 2007)
This research paper is to investigate the macroeconomic variables that influence on non performing loans of two Islamic banks in Malaysia. Objective of this study is to investigate the relationship between non performing loans in Islamic bank and conventional bank with the gross domestic product (GDP), inflation rate, and money supply. This study used the single regression method to measure the relationship between dependent and independent variables from year 2000 until 2006. This study found that macroeconomic variables such as gross domestic product, inflation rate and money supply are the factors that influence non performing loans and have negative relationship with non performing loans.